Characterization, hemolysis and multidrug resistance among Aeromonas spp. isolated from Bhavani river, Erode, South India - P. Ponmurugan, A.J. Smitha, K. Arti, T.Vidyashri, P. Vinothini, R. Sowmya, B. Bagyalakshmi, D. Sridhar (Recent Research in Science and Technology, 2009)
A total of 87 strains of Aeromonas spp. were identified biochemically. The strains were isolated from 50 samples of water from Bhavani river Erode, Tamil Nadu, India. In the present study among 87 Aeromonas spp. the prevalence strain was identified as A.hydrophila (60.9%), while the other strains belonged to the species A. sobria (20.7%), A. caviae (11.5%) and A.salmonicida (6.9%). The virulence factors like hemolysin, lipase, and serine protease were present in 96%, 93% and 94% of the strains respectively. Antibiotic susceptibility of Aeromonas spp. was determined by disc diffusion method. All Aeromonas spp. were examined for resistance against 16 antibiotics. All strains showed 100% of resistance to Ampicillin,Carbenicillin and Cephalothin. The highest resistances encountered were 91.9% to streptomycin,90.8% to polymyxin-B, 85% to rifampicin while the rest were under 50%.In contrast all the strains were sensitive to cefotaxime.The present work highlights the important incidence of Aeromonas spp., with virulence potential and antimicrobial resistance, isolated from river bhavani.